Revitalização urbana: uma análise sobre mudanças realizadas nos espaços públicos da área central de Campina Grande–PB (2000-2016) - Diniz, Kaio Santos (2018)
This work aims to present the importance of the production of public space in the urban and political context of cities, focusing on the central area of Campina Grande - PB. We assume that public space is an instance of the geographic space in which political participation, the existence of conflicts, social interaction and forms of sociability emerge as a theoretical conceptual framework that supports the geopolitical study of cities. In view of such discussion, this work has the following guiding question: In what way is the public space produced? From this questioning, we can see the spatial, historical and current trajectory, perceiving changes regarding the use / appropriation, forms of sociability, coexistence and participation of society in the projects. Thus, the relevance of this work is through geographical reading, as a possibility of understanding the changes made over the years as production of the space elaborated - apparently - under the sign of the managers and the dynamics that the city goes through. Through a specialized literature on the subject, using dialectic materialism, we seek to show the latest changes undertaken in the central area as a locus of revaluation, whose previous condition is the discourse of urban intervention. After this analysis we conclude that the recent construction of the public space in the city center has gradually diminished its possibilities of informal meetings, shrinking political participation, as well as the idea of citizenship under the sign of insecurity. Finally, the work attempted to measure probable nuances of the production of public space, showing the agents, interests involved, the clash between the public-private and the persistent forms of resistance as a way to contribute to other research in the area.